The Character of Electronic-Based Government System in Medium-Term Cities or Regencies Development Planning in the Province of Central Java in 2021-2026 - hermawan hermawan rudjito; Suharyo Joko Purnomo (Jurnal Politik Indonesia: Indonesian Political Science Review, 2023)
Electronic-Based Government System or digitalization of governmental management is a significant portion of Middle-Term Region Development Planning. It supports e-government programs that aim to realize a good and clean governance. The explanation of this topic must have coherence between chapters. This research seeks to examine the coherence in formulating the document, starting from identifying constraints in the development progress and the problem statement process until the activity programs of digitalization of governmental management to realizethe Mayor or Regent’s visions and mission. The method used is descriptive qualitative. Data sources use the document of Middle-Term Region Development Planning (RPJMD) prepared by cities and regents in the province of Central Java. Data analysis uses an ex-Ante examination model, which verifies the coherence between the discussion on identifying constraints of development practices, the problem statement process, and the effort to realize visions and missions of the development. The result reveals that 85.72% of the document prepared by the cities and regents has already been coherent between chapters. Nevertheless, while research analyzes cohesive consistency between the topics and sub-topics, just 23.81% of documents prepared by cities and regents fulfill the requirements. Consistent with coherence in the digitalization of governmental management on either discussion and total score, the documents prepared by the Regent of Kebumen and the City of Semarang achieved the highest score. Both documents are just 9.52% of the entire documents in the province of Central Java.